Effects of psycho-education plus basic cognitive behavioural therapy strategies on medication-treated adolescents with depressive disorder in Nigeria. Issue 1 (18th May 2018) - Isa, Ehimwenma W; Ani, Cornelius; Bella-Awusah, Tolulope; Omigbodun, Olayinka
Abstract : Objective: Limited data exists on psychological interventions for adolescent depression in African countries such as Nigeria. This study therefore investigates the effects of a psychological intervention that includes psycho-education and basic elements of cognitive behavioural therapy (CBT) on depressed medication-treated adolescents in Nigeria. Methodology: This was a pre-post one-group intervention study of 18 adolescents aged 13–18 years with clinically diagnosed depressive disorder, attending a specialist psychiatric hospital. They had been on antidepressants for 3 months or longer. Depressive symptoms, knowledge of depression, hope, and attitudes towards treatment adherence were measured at baseline and repeated at 1 and 4 weeks post-intervention. The adolescents received four sessions of a group-based manualised intervention focused on psycho-education and basic CBT strategies. Results: Statistically significant reductions in depressive symptoms were recorded, as were improvements in the adolescents' knowledge of depression, hope, and attitude towards treatment adherence one week after the intervention (all p = 0.001). All differences were sustained at 4 weeks post-intervention. Participants' satisfaction with the intervention was high. Conclusion: This study suggests that adding psycho-education with elements of CBT to antidepressant treatment is feasible, acceptable and can produce further benefits to depressed adolescents in this region.